TRUST AND HABIT AS KEY SUCCESS ON DIGITAL CONSUMING BEHAVIOR IN INDONESIA MEDIATED BY BEHAVIOR INTENTION - Daduk Mansur; Ernie Sule; Dwi Kartini; Yevis Marty Oesman (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
Personal perception as a fundamental factor on consumer buying behaviour especially on online shopping, triggered by internet access all over the world. In Indonesia personality aspect becomes a key factor regarding new technology adoption. Big internet user not yet automatically increased the use of e-commerce. Indonesia has big potential market for e-commerce. Unfortunately, the e-commerce user in Indonesia is still 12% from total internet user in Indonesia. It is very important to find factors i.e. Trust (T) and Habit (H), which affects the use behaviour of e-commerce. This study aims to find out the perfect model that fits the use behaviour of e-commerce in Indonesia. In this study,we conduct literature review and primary data survey. Statistical result is analysed using war Partial Least Square (PLS) with 547 respondents from 4 e-commerce providers user. We found that T (Trust) and H (Habit) have positive influence on Behaviour Intention (BI), BI positive influence on Use Behaviour (UB) e-commerce. Based on the results, we build a fit model and validate the data regarding e-commerce user behaviour. The fit model is expected to guide provider to find the key success factor in e-commerce business in Indonesia and are expected to become an innovation and important factors as an academic contribution. Based on these results we recommend operator to build good perception regarding Habit (H) and Trust (T). Keywords: Habit; Trust, Behavior Intention, Use Behavior